"Wrapped" nitrogen-doped defective reduced graphene oxide (ND-rGO): A virtual electron bed for enhanced supercapacitive charge storage in stepped-surfaced-NiCo2O4/ND-rGO||Bi2O3 asymmetric device. (1st April 2020) - Paliwal, Mahesh Kumar; Meher, Sumanta Kumar
Abstract: In the context of low impedance electron transfer in electrochemical charge storage devices, stepped-surfaced solids are important because they provide low work function and suitable interface for electron transfer. Contextually, in this work, for the first time, a carbonate-assisted synthesis method is adopted to fabricate severely stepped-surfaced porous NiCo2 O4 . Further, N-doped defective rGO (ND-rGO) wrapped NiCo2 O4 is assembled, and the electron bedding effect of ND-rGO on the supercapacitive charge storage performance of NiCo2 O4 is thoroughly studied. The physicochemical studies authenticate restricted crystal growth of NiCo2 O4 on ND-rGO and chemical bonding between ND-rGO and NiCo2 O4 . Detailed electrochemical studies using cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) and electrochemical impedance spectroscopy (EIS) techniques show redox-mediated charge storage in NiCo2 O4, ND-rGO-induced enhanced high-rate supercapacitive charge storage and lower charge-transfer resistance, equivalent series resistance and Warburg resistance in NiCo2 O4 /ND-rGO heteronanocomposite. Further, for the first time, Bi2 O3 was used as a super compatible negative electrode material to fabricate asymmetric supercapacitor (ASC) devices based on pristine NiCo2 O4 and NiCo2 O4 /ND-rGO, and in depth electrochemical characterizations show redox-capacitive charge storage behaviour in both the devices. The NiCo2 O4 /ND-rGO||Bi2 O3 demonstrates 2-times more areal capacitance at extreme rate condition, lower iR drop, very low charge transfer resistance, solution resistance and ion-diffusion resistance, as compared to NiCo2 O4 ||Bi2 O3 ASC device. The NiCo2 O4 /ND-rGO||Bi2 O3 ASC device also retains a very high 93.1% of specific capacitance after 5000 GCD cycles at an extreme applied current density of 32 mA cm −2 . Further, the NiCo2 O4 /ND-rGO||Bi2 O3 offers twice the energy density as compared to NiCo2 O4 ||Bi2 O3 ASC device, at elevated power density up to ∼10, 000 Wh kg −1 . The enhanced supercapacitive performance of NiCo2 O4 /ND-rGO||Bi2 O3 ASC device is ascribed to electron bedding effect of wrapped ND-rGO which provides a continuous conducting network, ND-rGO induced improved wettability, activated NiCo2 O4 |ND-rGO interface, and excellent electromechanical properties of NiCo2 O4 /ND-rGO heteronanocomposite. Graphical abstract: Image 1 Highlights: N-doped defective-rGO (ND-rGO) wrapped stepped-surfaced-NiCo2 O4 is prepared using (NH4 )2 CO3 as a novel precipitating agent. Wrapped ND-rGO acts as a virtual electron bed for unimpeded electron transfer during supercapacitive charge storage process. Bi2 O3 is used as a negative electrode material for the fabrication of NiCo2 O4 /ND-rGO||Bi2 O3 ASC device. The NiCo2 O4 /ND-rGO||Bi2 O3 ASC device shows enhanced capacitance and lower charge transfer & ion-diffusion resistance. At high power density, the ND-rGO/NiCo2 O4 ||Bi2 O3 delivers 200% more energy density than the NiCo2 O4 ||Bi2 O3 ASC device.